Melatonin prevents mitochondrial dysfunction and promotes neuroprotection by inducing autophagy during oxaliplatin‐evoked peripheral neuropathy. Issue 3 (1st March 2017) - Areti, Aparna; Komirishetty, Prashanth; Akuthota, Manasaveena; Malik, Rayaz A.; Kumar, Ashutosh
Abstract: Oxaliplatin, an organoplatinum compound, is used in the treatment of colorectal cancer, but its clinical use can be limited due to the development of peripheral neuropathy. Whilst mitochondrial dysfunction has been implicated as a major pathomechanism for oxaliplatin‐induced neurotoxicity, the prevention of autophagy may also aggravate neuronal cell death. Melatonin, a well‐known mitoprotectant and autophagy inducer, was used to examine its neuroprotective role in oxaliplatin‐induced peripheral neuropathy (OIPN). Melatonin prevented the loss of mitochondrial membrane potential (Ψm) and promoted neuritogenesis in oxaliplatin‐challenged neuro‐2a cells. It did not interfere with the cytotoxic activity of oxaliplatin in human colon cancer cell line, HT‐29. Melatonin treatment significantly alleviated oxaliplatin‐induced pain behavior and neuropathic deficits in rats. It also ameliorated nitro‐oxidative stress mediated by oxaliplatin, thus prevented nitrosylation of proteins and loss of antioxidant enzymes, and therefore, it improved mitochondrial electron transport chain function and maintained cellular bioenergetics by improving the ATP levels. The protective effects of melatonin were attributed to preventing oxaliplatin‐induced neuronal apoptosis by increasing the autophagy pathway (via LC3A/3B) in peripheral nerves and dorsal root ganglion (DRG). Hence, it preserved the epidermal nerve fiber density in oxaliplatin‐induced neuropathic rats. Taken together, we provide detailed molecular mechanisms for the neuroprotective effect of melatonin and suggest it has translational potential for oxaliplatin‐induced neuropathy. Abstract : Schematic model of mitoprotective and neuroprotective mechanisms of melatonin against oxaliplatin‐evoked peripheral neuropathy.